Dielectric spectroscopy and magnetometry investigation of Gd-doped strontium titanate ceramics. Issue 6 (June 2017) - Tkach, Alexander; Amaral, João S.; Amaral, Vitor S.; Vilarinho, Paula M.
Abstract: Structural, dielectric and magnetic properties of dense Gd-doped strontium titanate ceramics prepared by the conventional mixed oxide method are studied. Lattice parameter is found to decrease linearly in the Sr1-1.5 x Gd x TiO3 system, confirming the incorporation of Gd onto the Sr site of the perovskite lattice of strontium titanate up to x = 0.05. Real and imaginary parts of the dielectric permittivity of Sr1-1.5 x Gd x TiO3 ceramics exhibit a relaxation between 100 Hz and 1 MHz in the temperature range of 17–26 K, slightly shifting to higher temperatures with increasing Gd content. Such dielectric behaviour is attributed to the relaxation of individual dipoles formed by off-centre displacement of Gd 3+ ions on Sr sites in a highly polarizable lattice of strontium titanate. Other dielectric relaxations observed in Sr1-1.5 x Gd x TiO3 from 125 to 300 K are attributed to the oxygen vacancy related mechanisms. No magnetic anomaly but paramagnetic behaviour is observed for Sr1-1.5 x Gd x TiO3 ceramics, indicating an absence of the magnetic order and hence magnetoelectric coupling.